2012
DOI: 10.1002/art.37741
|View full text |Cite
|
Sign up to set email alerts
|

Activation of human synovial mast cells from rheumatoid arthritis or osteoarthritis patients in response to aggregated IgG through Fcγ receptor I and Fcγ receptor II

Abstract: Methods. Synovial tissue specimens were obtained from patients with RA or patients with osteoarthritis (OA) who were undergoing joint replacement surgery, and synovial MCs were enzymatically dispersed. Cultured synovium-derived MCs were generated by culturing synovial cells with stem cell factor, and receptor expression was analyzed using fluorescenceactivated cell sorting. Mediators released from MCs were measured using enzyme immunoassays or enzymelinked immunosorbent assays. Results. Primary synovial MCs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 77 publications
(99 reference statements)
2
38
0
Order By: Relevance
“…We recently reported that following the aggregation of FcγRI, SyMCs produced approximately 7 times more TNF-α than IFN-γ-treated human lung MCs, IFN-γ-treated human peripheral blood-derived cultured MCs or human peripheral blood mononuclear cells [15,18,19]. Taken together, the current data suggest that IL-33-dependent MC activation may exaggerate the inflammatory responses in the joint tissues of patients with RA by upregulating TNF-α and IL-8 production in MCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that following the aggregation of FcγRI, SyMCs produced approximately 7 times more TNF-α than IFN-γ-treated human lung MCs, IFN-γ-treated human peripheral blood-derived cultured MCs or human peripheral blood mononuclear cells [15,18,19]. Taken together, the current data suggest that IL-33-dependent MC activation may exaggerate the inflammatory responses in the joint tissues of patients with RA by upregulating TNF-α and IL-8 production in MCs.…”
Section: Discussionmentioning
confidence: 99%
“…Cultured human SyMCs were generated as described previously after synovial tissues were enzymatically dispersed [15]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are in agreement with recent immuno-histological studies demonstrating that in a small subset of intestinal MCs FcγRI is expressed during homeostasis, but that the frequency of FcγRI + MCs is strongly increased in patients with Crohn’s disease, a disease which is associated with increased IFN-γ levels [32]. The FcγRI + expression profile in intestinal MCs is very similar to what has been reported for MCs derived from peripheral and cord blood as well as skin and synovial MCs, which express no or very low levels of FcγRI + after culture with SCF [14,33-35]. However, in peripheral blood-dervied MCs FcγRI expression can be induced by IFN-γ [14], and immuno-histological studies showed that skin MCs are negative for FcγRI expression during homeostasis, while FcγRI expression can be detected in MCs of tissue samples derived from patients with psoriasis [36].…”
Section: Discussionmentioning
confidence: 79%
“…In mice, certain mast cell subsets, including synovial mast cells, express the activating FcγRIIIa (Benhamou et al, 1990;Fang et al, 2013;Latour et al, 1992), the receptor involved in arthritis induced by anti-collagen autoantibodies (Díaz de Ståhl et al, 2002). Human mast cells have been shown to express FcγRIIA, whereas there is some controversy regarding expression of FcγRI (Jonsson et al, 2012;Lee et al, 2013;Suurmond et al, 2014a). We have recently shown that human cultured mast cells could be activated by ACPA immune complexes in a citrulline-dependent manner (Suurmond et al, 2014a).…”
Section: Mast Cell Activation By Autoantibodiesmentioning
confidence: 99%